Aplikasi Hidrogel Poli-(akrilamida) Hasil Iradiasi Gamma untuk Adsorpsi Zat Warna Biru Metilen dalam Larutan - Erizal; Winarno, Hendig; Abbas, Basril (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
The aim of theresearch is to study the capacity of poly(acrylamide)(PAAM) hydrogel to adsorp a syntheticdye of methylene blue (MB). PAAM hydrogel was synthesized by varying gamma radiationdoses (20-40 kGy), and was then processed to dried powder (120 mesh) and used to adsorbMB dye from the aqueous solution. The batch adsorption experiment was carried out byvarying contact time (0-120 min.), initial concentration of MB (2-10 mg/L), adsorbent dose (0-120 mg), and the chemical changes of hydrogels were characterized by Fourier Transforminfra red (FTIR). The adsorption process of MB was examined with Langmuir and Freundlichisotherm models. The results showed that the hydrogel prepared at 20 kGy had higheradsorption capacities onto MB compare to the hydrogel at 30 and 40 kGy. With increasinghydrogel doses, the MB adsorbed increase. The results of Langmuir and Freundlich isothermexamination obtained the coefficient correlation (R2) of 0,9914 and 0,9964 with maximumadsorption capacity 1.67 mg/g at a solution pH of 6.5. Modification of PAAM hydrogels willbe potentially as dyes adsorbent.